ANALISIS PENDAPATAN PETANI PADI SAWAH DI DESA SIHEPENG KECAMATAN SIABU KABUPATEN MANDAILING NATAL PROVINSI SUMATERA UTARA - Endro Freddy; Roza Yulida; Evy Maharani (Indonesian Journal of Agricultural Economics, 2017)
Agricultural extension is part of the national life, especially farmers, and important in promoting the general welfare and one of the keys to the success of strengthening farmer groups. The purpose of this research are: 1) to analyze the cost of production of paddy rice farming in the village Sihepeng Siabu District Mandailing Natal Regency of North Sumatera Province and 2) to analyze the income of rice farmers in Sihepeng Village, Siabu District Mandailing Natal Regency. This study was conducted from May to July 2015. The method used in this study was survey and sampling techniques used was disproportionate stratified Random Sampling. The sampling was 50% of the population, consisting of 54 beginner-class farmers, 9 advanced-class farmers. The results showed the average total cost of production of 0.1-1 ha land area was IDR 3.321.868 and the average total cost of production land area > 1 ha was IDR 18.840.333. Total net income received by farmers with land area of 0,1-1 ha was IDR 545.132.800 with an average income of IDR 8.016.659. Total net revenues received by farmers with land area of > 1 ha was IDR 638.586.400 with an average net income of IDR 42.572.427. Comparison of the results of the income of farmers with an area of 0.1-1 ha of rice field and > 1 ha much greater level of income of farmers in land area > 1 ha due to differences in the area of land owned by farmers. Results expected that the income of farmers in Sihepeng Village with a land area of 0.2 ha to be more efficient in the utilization of paddy fields.